PENGARUH PENGGUNAAN BAHAN AJAR NON CETAK BERMUATAN KARAKTER MENGGUNAKAN PENDEKATAN SAINTIFIK TERHADAP KOMPETENSI SISWA PADA MATERI GELOMBANG MEKANIK KELAS XI SMA NEGERI 3 PADANG - Fran Surya Andi; Yenni Darvina; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2017)
This research aims to find out the large influence of the use of printed non-printed teaching materials character using scientific approach to the achievement of student competence is limited to mechanical wave material in SMA N 3 Padang. The type of research used is pre-experimental designs with One-Group Pretest-posttest Design research. In this research, experiments conducted by without controlling for influencing variables are treatment alone without any control group. The result of data analysis shows that in the comptence attitude, the average value obtained by students has increased every meeting. On knowledge competence got value y = 0,49x + (- 50,37), value r = 0,83, and value of KD = 68,94%. In skill competence obtained value y = 0,52x + 44,98, value r = 0,50, and value of KD = 25,14%. The working hypothesis which reads "there is influence which means the use of printed non-print teaching materials using a saintifik approach to student competence on mechanical wave material of class XI SMAN 3 Padang" is quantitatively acceptable at the real level of 0,05. Thus, the use of printed non-printed teaching materials using characteristic scientific approaches to student competence